The big secret for the small investor : a new route to long-term investment success - Greenblatt, Joel. (Chichester, UK : John Wiley & Sons, 2011)
Joel Greenblatt, the founder of investment giant Gotham Capital, presents a quintessential guide to safe investing. Here he teaches small investors tips and techniques that can offer them short-term stability and long-term success.
Keywords: Investments; Portfolio management; Stocks